Artificial intelligence and the redefinition of the accounting profession - Kottara, Chara; Kavalieraki-Foka, Dimitra; Asonitou, Sofia (Journal of Accounting, Business and Finance Research, 2026)
Digitalization has radically impacted the role of the accountant from bookkeeping, to accounting standardization and consulting. The integration of Artificial Intelligence (AI) into the accounting profession is shaping a new context and the need to acquire analytical thinking and decision-making skills. This study was conducted using desk-based research methodology, to examine the impact of artificial intelligence in the accounting sector. The findings suggest a strong positive contribution of artificial intelligence, mainly through reducing data processing time, improving the accuracy of results, and enhancing predictive capabilities. However, several challenges were identified, such as lack of training, ethical data management, and the high cost of integrating AI applications. It was found that the successful adoption of complementary technologies, such as blockchain and the development of personalized reports, are directly dependent on the technological infrastructure, the continuous education of accountants, and the effective resolution of both technical and ethical issues.